The Wealth of Mexican Americans - Vincent A. Hildebrand; Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2004)
This paper analyzes the sources of disparities in the relative wealth position of Mexican Americans. Results reveal that wealth gaps are in large part not the result of differences in conditional expected wealth functions. Similarly, income differentials are important, but do not play the primary role in explaining the gap in median net worth. As much or more of Mexican Americans? wealth disadvantage is attributable to the fact that these families have more young children and heads who are younger. Furthermore, Mexican Americans? low educational attainment has a direct effect in producing a wealth gap relative to other ethnic groups (even after differences in income are taken into account) though education does not significantly affect the nativity wealth gap. Finally, geographic concentration is generally unimportant, but does contribute to narrowing the wealth gap between wealthy Mexican Americans and their white and black counterparts.
Keywords: J10; G11; J61; 330; wealth; Mexican Americans; Vermögensverteilung; Familiensoziologie; Bildungsniveau; Mexikaner; Vereinigte Staaten